2019
DOI: 10.3390/w11071373
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change and Associated Vegetation Cover Change on Watershed-Scale Runoff and Sediment Yield

Abstract: Climate change has an important impact on water balance and material circulation in watersheds. Quantifying the influence of climate and climate-driven vegetation cover changes on watershed-scale runoff and sediment yield will help to deepen our understanding of the environmental effects of climate change. Taking the Zhenjiangguan Watershed in Sichuan Province, China as a case study, three downscaled general circulation models with two emission scenarios were used to generate possible climatic conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 57 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…Getahun and Lanen [86] reported projected change in main rainy season precipitation with less than ±20% in all GCMs in the Upper Awash River Basin. The predicted increase of precipitation was unevenly distributed in a year, which would further increase the seasonal variation of precipitation in the watershed [19].…”
Section: Future Climate Projectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Getahun and Lanen [86] reported projected change in main rainy season precipitation with less than ±20% in all GCMs in the Upper Awash River Basin. The predicted increase of precipitation was unevenly distributed in a year, which would further increase the seasonal variation of precipitation in the watershed [19].…”
Section: Future Climate Projectionmentioning
confidence: 99%
“…The rising GHG concentration due to continued gas emissions from different sources to the atmosphere affects climate variables and consequently alters hydrological cycles [10,[12][13][14][15]. The change in climate-mainly due to precipitation and temperature patterns-could significantly influence soil erosion rates, streamflow, and sediment yield, which (directly or indirectly) adversely affects water resource availability and ecosystems [13,[16][17][18][19]. In connection to this, numerous studies have indicated that changes in precipitation, temperature, and the interactions of these with land use and land cover change (LULCC) will be the main climate change related stress expected to exacerbate soil loss and sediment transport [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The processes of soil erosion and sediment transport take part in van Rijn's (1993) [3] sedimentary cycle, and often are the main causes of soil loss in basins [4]. Although these processes are of natural origin [5], the interaction between climate, soil, topography, land use, and land cover significantly influence erosion rates and sediment loads [6,7]. Soil loss due to these processes is a frequent problem that hydrologists, land planners and basin managers will need to deal with [8].…”
Section: Introductionmentioning
confidence: 99%